THE METHOD OF TREATMENT OF GENERALIZED CYTOMEGALOVIRUS INFECTION IN INFANTS - S. S. Kochkina; E. P. Sitnikova (Детские инфекции (Москва))
Purpose of the study. Evaluation of the effectiveness of treatment of generalized cytomegalovirus infection (CMVI) in infants with a combination of ganciclovir and VIFERON®.Materials and methods. 52 children of the first months of life were treated with generalized CMV. Patients are divided into 3 groups: the first included 25 children who received ganciclovir for 14—21 days, then — IFN-α-2b in combination with antioxidants vitamins E and C (VIFERON®); The second group consisted of 17 patients receiving only ganciclovir; in the third group included 10 children who had only symptomatic treatment of CMVI: hepatoprotectors, broad-spectrum antibiotics (ceftriaxone, ampicillins) at age dosages. Therapy was carried out under the control of viral load in the blood serum on the 14th and 21st day from the start of treatment. Patients of the 1st group with a decrease in the clinical manifestations of CMV and a decrease in the viral load to 104—103 copies/ml on the 14—21 day were prescribed rectal suppositories of IFN-α-2b (VIFERON®) 150 000 IU according to the original scheme.Results. In the 1st group, all children during 3—6 months had an elimination of the virus from the blood and liquor. Relapse of CMV was not observed. Children of the second group had a decrease in the viral load was observed, but the elimination of the virus from the blood, the cerebrospinal fluid did not occur. Patients of the 3rd group had the viral load remained at the same level, it increased by 102 copies/ml at one patient.The conclusion. Using of combined antiviral therapy with ganciclovir and IFN-α-2b in combination with antioxidants vitamins E and C (VIFERON®) promotes elimination of the virus from blood and liquor, transferring and keeping it in an inactive state, which prevents the development of complications. The proposed method for treatment of CMV can be successfully used in inpatient and outpatient settings.